Experience implementing a mentoring program for incoming students at Faculty of Dentistry - Ortiz Fernández, Lita (2011)
The purpose of this study was to evaluate the development of mentoring process and performance of the tutor in a mentoring pilot program from the perspective of student and teacher, the research design is pre experimental, application, qualitative and quantitative, the group consisted of 61 students and 12 tutors. This research had three stages; in the first teachers were trained as tutors with e-learning and was opened a virtual classroom. In the second stage was made some groups, the incoming student's profile was identified, in the third stage was performed the mentoring program and was evaluated.Results: 44% of students attend quite frequently and regularly to the tutoring program, while 6 teachers were constant. Students and teachers assessed three positive actions of tutor performance, the goals for the tutoring program were setting together, the support in the design of the plan was according to the needs, it was created a favorable climate for communication. While the negative topic was the systematic monitoring of the activities and agreements with the student, which they attribute to lack of time by 90%, since they have not assigned a schedule in the curriculum. Mentoring requires institutional policy decision for implementation also the work coordinated with the academic and administrative areas,to record greater achievements, but it had limitations because it was a pilot project. Tutoring allows evidence student’s empowerment with more autonomy and a creative criticism and showed tutor’s effort to improve student’s skills.